Correlation of Regional Taxes and Regional Expenditures on Regional Fiscal Capacity Parigi Moutong District - Cicilia, Vera Sri Endah; Suirlan, Rita; Rafika, Ika; Achmad, Nuryana Haprin DJ (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the relationship between regional taxes and regional expenditure on the regional fiscal capacity of Parigi Moutong Regency 2016-2022. The research method uses a quantitative approach with a total of 7 years of observations obtained from the Regional Financial and Asset Management Agency Report of Parigi Moutong Regency and analyzed using simple linear correlation (least square method). The research results show that the regional tax variable is positively and significantly correlated with the regional fiscal capacity of Parigi Moutong Regency. The regional expenditure variable has a negative and insignificant correlation with the regional fiscal capacity of Parigi Moutong Regency. The results of this research illustrate the importance of optimizing regional taxes through intensification, extensification, and using the budget effectively and efficiently so as to create regional independence. The limitations of this research are that it does not cover all the dominant variables that support regional fiscal performance and still uses relatively small data.